SOCIAL AND ETHICAL IDEAS IN ABDULLAH IBN MUQAFFA’S “AL-ADAB AL-KABIR” (Western European Journal of Historical Events and Social Science, 2026)
This article explores the social, ethical, and political ideas presented in Abdullah ibn Muqaffa’s “al-Adab al-kabir”. It provides a comprehensive analysis of the author’s perspectives on moral conduct, civic responsibility, justice, and governance, highlighting their significance within the broader framework of early Islamic thought. The study demonstrates how Ibn Muqaffa combines ethical principles with practical guidance for rulers and members of society, emphasizing the interconnection between personal virtue, social harmony, and political authority. By situating “al-Adab al-kabir” within the tradition of the Islamic siyasatnama literary genre, the article illustrates the continuity of moral-political discourse in classical Islamic literature and its relevance for understanding the ethical foundations of governance and social order. The research also sheds light on the ways in which Ibn Muqaffa’s ideas reflect both universal ethical concerns and the specific historical and cultural context of the Abbasid period.